PROTEIN SPECTRUM OF PIGLETS’ BLOOD SERUM UNDER THE INFLUENCE OF FERRUM PREPARATIONS - Dukhnitsky, V. B.; Derkach, I. M.; Derkach, S. S.; Lozovyі V. M.; Kostrub, V. V.; Losa, Yu. V.; Fritsky, I. O.; Plutenko, M. O. (Scientific Progress & Innovations, 2021)
At present, using ferrodextran preparations is considered the most simple and effective method of piglets’ treatment for anemia and its prevention. However, this method has a number of disadvantages. Thus, alt-hough the problem of iron deficiency has been studied for a long time, it is still relevant today. The aim of our study was to determine the effect of ferrum (IV) clatrochelate on the blood serum protein spectrum of piglets when administering the preparation to pregnant sows in order to prevent iron deficiency anemia in piglets born to them. To achieve this goal, 2 groups of newborn piglets-analogues (hybrids of Landrace and Large White breeds) were formed during the period of their keeping with nursing sows – control and exper-imental, 15 animals in each. The research and production experiment, which lasted 30 days, was based on determining the effect of iron (IV) clatrochelate on the piglets’ organism born to sows that were twice ad-ministered intramuscular with the solution of the studied preparation during their pregnancy. As a result of our research, we did not observe the birth of dead piglets and any clinical signs of anemia. The content of albumin throughout the experiment was slightly higher in the blood serum of piglets in the experimental group as compared with the control. The increase in the level of total protein and its main fraction – albu-mins in the blood serum of piglets in the experimental group indicates the activation of the anabolic way of protein metabolism and the predominance of synthesis processes. The content of β-globulins at the beginning of the experiment on the 30th day probably exceeded the control value. The level of γ-globulins on the 5th day in the blood serum of piglets in the experimental group was 1.2 times higher as compared with the control, but on the 30th day, on the contrary, it was 1.2 times lower. The studies of the blood serum protein spectrum of piglets under the influence of ferrum preparations confirm that the proposed scheme for the prevention of iron deficiency anemia was effective.